Can Secular Law Be Understood as Sharia Law? A Philosophical Exploration - Husni Husni; Miftahul Khairat; Hidayatina Hidayatina (Qiyam Islamic Studies Center Foundation, 2025)
This article aims to philosophically examine whether secular law can be conceptually situated within the framework of sharia law by reinterpreting ḫiṭābullāh ta‘ālā as encompassing not only revealed texts but also natural and social phenomena. Employing a qualitative normative approach through conceptual and textual analysis of classical uṣūl al-fiqh literature, maqāṣid al-ṧarī’aḧ theory, and contemporary legal discourse, this study analyzes the epistemological and theological foundations of law formation. The findings demonstrate that secular law embodying universal values such as justice, public welfare, human dignity, and environmental balance may function as a medium for conveying ḫiṭābullāh within the category of the “open book” (al-kitāb al-maftūḥ), and can be integrated into Islamic legal reasoning through mechanisms of ijtihād, ‘urf, and maṣlaḥaḥ mursalaḥ, provided it remains consistent with the fundamental objectives of sharia. The study concludes that secular law and sharia law are not inherently antagonistic but potentially complementary, with maqāṣid-oriented reasoning enabling Islamic law to respond elastically to modern socio-legal realities, albeit with significant theological and legal implications such as a shift toward anthropocentric interpretation and the emergence of hybrid legal structures. This article contributes academically by offering a reconceptualization of ḫiṭābullāh and a philosophical framework for harmonizing sharia law with secular legal systems without reducing Islamic law to mere pragmatic legitimation.